2012
DOI: 10.1017/s0954579412000478
|View full text |Cite
|
Sign up to set email alerts
|

Testing multiple levels of influence in the intergenerational transmission of alcohol disorders from a developmental perspective: The example of alcohol use promoting peers and μ-opioid receptor M1 variation

Abstract: This study examined the interplay between the influence of peers who promote alcohol use and μ-opioid receptor M1 (OPRM1) genetic variation in the intergenerational transmission of alcohol use disorder (AUD) symptoms while separating the “traitlike” components of AUD symptoms from their age-specific manifestations at three ages from emerging adulthood (17–23 years) to adulthood (29–40 years). The results for males were consistent with genetically influenced peer selection mechanisms as mediators of parent alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…Genetic susceptibility for substance use and peer selection are correlated, but likely attributed to other genes than those for alcohol metabolism (40,41). For example, Chassin et al (42) and Mrug and Windle (43), respectively, studied dopamine receptor ( DRD4 ) and μ-opioid receptor M1 ( OPRM1 ) genes in association with alcohol use behaviors and found evidence for both genetically influenced peer selection and gene–environment interaction. These interactions, as with the current study, showed stronger risk allele effects with greater peer influences.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility for substance use and peer selection are correlated, but likely attributed to other genes than those for alcohol metabolism (40,41). For example, Chassin et al (42) and Mrug and Windle (43), respectively, studied dopamine receptor ( DRD4 ) and μ-opioid receptor M1 ( OPRM1 ) genes in association with alcohol use behaviors and found evidence for both genetically influenced peer selection and gene–environment interaction. These interactions, as with the current study, showed stronger risk allele effects with greater peer influences.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype frequencies did not deviate significantly from Hardy-Weinberg equilibrium, χ 2 (1, n = 116) = 2.92, p = .09. Participants were dichotomized as either G allele carriers (A/G, G/G; n = 37, 32%) or noncarriers (A/A; n = 79, 68%) consistent with previous research (Chassin et al, 2012; Miranda et al, 2013) and suggestions that a cross-product G×E interaction term using a three-category polymorphic genotype may increase false positive and negative findings (Aliev et al, 2014). Although social drinking conditions were not stratified by genotype due to random assignment, participants were generally evenly distributed across the 0 ( n = 13 for carriers, n = 25 for noncarriers), 1 ( n = 12 for carriers, n = 27 for noncarriers), and 3 ( n = 12 for carriers, n = 27 for noncarriers) confederate conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In a cross-sectional study of European-American adolescents ( N = 104), G allele carriers were more likely to meet criteria for an alcohol use disorder when endorsing high relative to low deviant peer affiliation (Miranda et al, 2013). In a longitudinal observational study ( N = 238), OPRM1 ’s G allele magnified the influence of heavy drinking peer affiliation (i.e., perceived peer drinking norms) among Caucasian women, but not men, on alcohol use disorder symptoms at 17–23 (but not 23–40) years of age (Chassin et al, 2012). Existing research on OPRM1 -based susceptibility to peer environments has been inconclusive and exclusively correlational.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control design of adolescents with alcohol use disorder (n=104), Miranda and colleagues [48] found that a higher proportion of the high-risk G allele carriers (AG/GG genotype) met criteria for alcohol use disorder compared to the low risk AA homozygotes and this effect was amplified when parental monitoring was low and deviant peer affiliation was high. Using a larger sample (n= 529), Chassin and colleagues [49] found that exposure to deviant peers was associated with higher levels of alcohol use disorder symptoms for women (but not men) who were G allele carriers, but women with the AA genotype were not as susceptible to deviant peer influences.…”
Section: Moderators Of Dopamine and Opioid Genesmentioning
confidence: 98%